PROTOTYPE OF TRADITIONAL MINED CRUDE OIL DISTILLATION TECHNOLOGY - Islakhul Umah Arif; Basyirun Basyirun (Jurnal Dinamika Vokasional Teknik Mesin, 2023)
Crude oil or petroleum is a complex hydrocarbon compound consisting of carbon, hydrogen, and a small number of other elements such as oxygen, nitrogen, sulfur, and several metals including Fe, Na, Va, all of which are impurities. In Wonocolo there is a traditional oil mining relic from the Dutch era carried out by local residents. Oil from traditional mining is processed by residents into diesel fuel by simple distillation. Petroleum distillery equipment which is still simple has several drawbacks, namely the process is carried out openly, condenser heat transfer is not optimal along with the distillation process, and causes air pollution in the surrounding environment. This study aims to design a laboratory-scale distillation prototype that has the characteristics of setting the cooling water discharge in the condenser, the effect of time on the distillation capacity, and setting the boiler temperature on the prototype. The results of the prototype design for crude oil distillery have the following specifications; the capacity of the petroleum distillery process is 5000 ml in the boiler, the boiler material uses stainless steel 201. The condenser uses a shell and tube type with counter flow flow direction, with a number of tubes 12 with a diameter of 19 mm and a length of 500 mm.The prototype characteristics in the 3-7 discharge test have the highest heat transfer value at 7 liters/minute discharge, which is 210.8 W and the lowest is 50.19 W at 3 liters/minute discharge. Characteristics of distillation time at 174.48 minutes can produce 3486.67 ml of diesel oil with a kitchen temperature of 350 oC. The characteristics of the kitchen temperature control from 310 oC, 330 oC, 350 oC, 370 oC, and 390 oC, the highest diesel oil was 4350 ml at 390 oC and the lowest was 1670 ml at 310 oC.